Cats, Postdramatic Blockbuster Aesthetics and the Triumph of the Megamusical - Vagelis Siropoulos (Image & Narrative, 2010)
Abstract (E): Despite its popularity, the megamusical is the most critically maligned and academically neglected form of theatre. Focusing on Cats (1981), the show that announced the megamusical’s global dominance, this article will try to provide a culturally informed analysis of megamusical aesthetics that explains the popularity of the genre in postmodern culture. Particular attention will be paid to the megamusical’s development of a commodified postdramatic, predominantly visual aesthetic, which informs other postmodern mass-cultural artifacts, like blockbuster films. To make possible the theorization of a commodified postdramatic aesthetic, the article will provide an intertextual reading of Hans-Thies Lehmann’s seminal work, Postdramatic Theatre, with the theories of the Tel Quel group (Roland Barthes, Julia Kristeva) as well as cultural theory, from Walter Benjamin to Fredric Jameson. Abstract (F): En dépit de sa popularité, la grande comédie musicale (« megamusical ») reste mal vue de la critique et totalement négligée par la recherché universitaire. Le présent article, qui porte sur Cats (1981), le show qui a lancé l’actuelle hégémonie de ce type de spectacle, offre une analyse culturelle du genre qui explique son succès en le rattachant à la culture postmoderne. Il s’intéresse tout d’abord à la manière dont la grande comédie musicale élaborer une certaine esthétique visuelle très commercialisée et postdramatique, qui caractérise aussi d’autres produits de la culture de masse postmoderne comme les films à gros budget. Dans ce but, cet article s’appuie surtout sur une lecture croisée du livre capital de Hans-Thies Lehmann, Postdramatic Theatre, ce certaines idées clé des membres du groupe Tel Quel (Roland Barthes, Julia Kristeva) ainsi que de certaines théories culturelles empruntées à Walter Benjamin et à Fredric Jameson.